1999
DOI: 10.1007/s11664-999-0034-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of silicon ion-implanted gallium nitride by furnace annealing

Abstract: Ion implantation into III-V nitride materials is an important technology for highpower and high-temperature digital and monolithic microwave integrated circuits. We report the results of the electrical, optical, and surface morphology of Si ion-implanted GaN films using furnace annealing. We demonstrate high sheet-carrier densities for relatively low-dose (n atoms = 5 × 10 14 cm -2 ) Si implants into AlN/GaN/sapphire heteroepitaxial films. The samples that were annealed at 1150°C in N 2 for 5 min exhibited a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…While the limited activation of dopants, including devices, via rapid thermal-annealing (RTA) topologies in conjunction with capping moieties has been demonstrated previously [16][17][18], there is a dearth of data showing low compensation, high mobility, and high efficiency. Specifically, concerning silicon implant activation, demonstrations as early as 1995 exhibited low mobility and n-type conductivity [19], while improvements in the following decade made by various groups [20][21][22][23] demonstrated activation efficiencies/mobilities of up to 68%/~100 cm 2 /Vs at a 1 × 10 15 cm −2 dose [21] and ~60%/240 cm 2 /Vs and 15%/112 cm 2 /Vs at 5 × 10 17 and 1 × 10 19 cm −3 donor concentrations, respectively [23].…”
Section: Introductionmentioning
confidence: 99%
“…While the limited activation of dopants, including devices, via rapid thermal-annealing (RTA) topologies in conjunction with capping moieties has been demonstrated previously [16][17][18], there is a dearth of data showing low compensation, high mobility, and high efficiency. Specifically, concerning silicon implant activation, demonstrations as early as 1995 exhibited low mobility and n-type conductivity [19], while improvements in the following decade made by various groups [20][21][22][23] demonstrated activation efficiencies/mobilities of up to 68%/~100 cm 2 /Vs at a 1 × 10 15 cm −2 dose [21] and ~60%/240 cm 2 /Vs and 15%/112 cm 2 /Vs at 5 × 10 17 and 1 × 10 19 cm −3 donor concentrations, respectively [23].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal activation of implanted dopants and the damage recovery of implanted GaN regions require annealing at temperatures above 1500 °C with a nitrogen atmosphere pressure more than 15 kbar at equilibrium [10], which is difficult to apply advantageously to the manufacture of normal ICs. Furthermore, high temperature annealing will lead to Ga dissociation from the GaN surface, resulting in a rough surface and also breaking the interface between AlGaN and GaN, hence the sheet concentration of 2DEG will be reduced [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to make the implanted ions optically and electrically active, it is required to anneal out the implantation damage-related defects without dissociation of host atoms. Previous studies have shown that the activation of implanted impurities in III-nitride materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] is much more difficult than for conventional compound semiconductors such as GaAs and InP. A number of articles 1-8 and reviews 9-10 reporting on ion implantation studies in GaN have been published.…”
Section: Introductionmentioning
confidence: 99%